2000
DOI: 10.1089/thy.2000.10.445
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-8 Levels in Thyroid Diseases

Abstract: Cytokines are likely to play an important role in auto¬ immune thyroid disease. These molecules are produced by both inflammatory cells and thyroid follicular cells and may affect the latter directly including expression of major histocompatibility complex class II molecules and adhesion mol¬ ecules (1-9).Interleukin-8 (IL-8) is a cytokine with neutrophil chemotactic/activating and T-cell chemotactic activity both in vivo and in vitro (10,11)· It is synthesized as a 99-amino acid pre¬ cursor and secreted as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Bossowski and Urban and Siddiqi et al have also observed significantly elevated levels of IL-8 in patients with Graves' disease and nodular goiter as compared to the respective healthy control groups [31, 32]. In contrast to these of studies, Krassas and colleagues found that IL-8 levels were not elevated in Graves' disease, toxic nodular goiter and Hashimoto's thyroiditis [33]. A study by Lee et al has shown increased levels of cytokines including IL-8 and IL-10 in patients who frequently developed euthyroid sick syndromes followed by allogeneic bone marrow transplantation [34].…”
Section: Resultsmentioning
confidence: 99%
“…Bossowski and Urban and Siddiqi et al have also observed significantly elevated levels of IL-8 in patients with Graves' disease and nodular goiter as compared to the respective healthy control groups [31, 32]. In contrast to these of studies, Krassas and colleagues found that IL-8 levels were not elevated in Graves' disease, toxic nodular goiter and Hashimoto's thyroiditis [33]. A study by Lee et al has shown increased levels of cytokines including IL-8 and IL-10 in patients who frequently developed euthyroid sick syndromes followed by allogeneic bone marrow transplantation [34].…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that overt hypothyroidism negatively affects reproduction and pregnancy outcomes via increased miscarriage rates, menstrual irregularities, subfertility, ovulation failure, and altered ovulatory function ( 15 , 16 ). However, it is unclear to what extent SCl hypoT affects pregnancy outcomes.…”
mentioning
confidence: 99%
“…However, it is unclear to what extent SCl hypoT affects pregnancy outcomes. Although this subject remains controversial, some studies have shown that pregnant patients with SCl hypoT have a significantly higher risk of placental abruption, preterm birth, stillbirths, and miscarriage ( 15 , 16 , 17 , 18 ). The treatment of SCl hypoT in pregnant patients has been found to positively impact miscarriage and live birth rates for those undergoing in vitro fertilization (IVF) and is associated with a decrease in obstetric and neonatal complications ( 19 ).…”
mentioning
confidence: 99%